Role of government, NGO and PO in promoting social capital for watershed management in Brgy. Abay, Maasin, Iloilo. - Ventura, Brian C
Using data reviewed from the secondary literature, personal interview, participant observation and quantitative survey questionnaire about the relationship of trust, cooperation and association from the government, NGO and PO, the study assessed the international national and local factors affecting the promotion of institutional social capital for watershed management . The study also identitified and examined the roles that the three actors assumed in the promotion of institutional social capital in the conduct of community organizing and strengthening activities. By triangulating the data gathered, the findings showed that the role that each actors assume is affected by factors in the international, national and local level through the localization of the Global Agenda 21 to Philippine Agenda 21 and the policy of the Japan Bank for International Cooperation (JBIC) as the international funding agency, environmental degradation and decentralization, importance of the watershed and the community's social condition. The government, or the DENR assumed its role in promoting institutional social capital in community organizing and strengthening activities by promoting institutional and policy frameworks, initiating vertical linkage with other government agencies and cross-sectoral linkage with a private organization. The NGO "crafted local institutions", promoted socio-political capital, acted as "discourse generators" and had a close coordination with the DENR. The PO promoted horizontal linkages, encouraged community participation by providing livelihood as an incentive, has informal relationships with formal orgnization and is connected with the institutional and policy framework of the DENR. The individual roles assumed by these actors engendered a hierarchical institutional arrangement in the promotion of social capital. In the quantitative data, there are disparities in the mean of the perception of actors on some items especially with regards to the performance of responsibilities and utilizationof funds that highlight the differences of the actors interests and priorties.